THE ROLE OF THE KARAWANG GOVERNMENT IN ADDRESSING ENVIRONMENTAL POLLUTION (AIR POLLUTION) CAUSED BY COMPANIES IN THE KARAWANG AREA - Harariawan Priyatna; Yuniar Rahmatiar; Suyono Sanjaya (Universitas Labuhanbatu, 2024)
Environmental pollution, especially air pollution, has become a serious problem in many countries including Indonesia. Industrial cities such as Karawang City have a big challenge in overcoming air pollution problems, which are mostly caused by the industrial sector and motorized vehicles. This research aims to find out what the Karawang government should do to overcome the pollution produced by factories in Karawang City and how effective the Karawang Regency Regional Regulation Number 14 of 2012 concerning Environmental Protection and Management is. In 2023, Karawang experienced very high levels of air pollution until the air quality index value reached 178. The impact of this was that many people were affected by ARI, even the smoke produced by factories in Karawang had an impact on Jakarta and surrounding areas. To address this air pollution problem, the Karawang government has a major role in accordance with the local regulation (Perda) on Environmental Protection and Management, that the government is responsible for establishing effective regulatory policies, taking firm action against business owners whose factories do not comply with government regulations, and supervising factories that have the potential to pollute the air. Although there are local regulations that deal with air pollution problems, in reality these regulations are not fully effective, because there are still many factories that do not comply with the rules and the sanctions given are not burdensome and provide a deterrent effect, so the government needs to evaluate the regional regulation in dealing with air pollution problems in Karawang City.Keywords: air pollution; government; industrial area